Organization strategies in the Rey-Osterrieth Complex Figure in children with ADHD - Josefina Rubiales; Daiana Russo; Rocío González; Liliana Bakker (European Journal of Investigation in Health, Psychology and Education, 2017)
The aim of this study was to analyze ADHD diagnosed children´s process of copy, organization strategies and recall phase of Rey-Osterrieth Complex Figure. This study corresponds to an ex post facto retrospective design with two groups, one quasi control. Seventy children between 8 and 14 years old were evaluated; 35 with ADHD and 35 without these diagnoses, paired by sex, age and instruction level. To reach the proposed objective, the process of copying, organizational strategies and memory of the Rey-Osterrieth Complex Figure were evaluated. The Rey-Osterrieth Complex Figure is a test which consists of copying phase and posterior playing back memory phase of a complex geometric pattern. Results showed a lower yield for the group with ADHD both in copy and memory process, with greater use of C and D types of copy reproduction, being the use of type D expected for younger children. These results allow further analysis of the performance of children with ADHD regarding organizational strategies providing expertise in the conceptualization, evaluation and treatment of the disorder.